Gut leakage and cardiac biomarkers after prolonged strenuous exercise in highly trained endurance athletes - Aune, S. K.; Bonnevie-Svendsen, M.; Nyborg, C.; Trøseid, M.; Seljeflot, I.; Hisdal, J.; Helseth, R. (Atherosclerosis, 2022)
Background and Aims: Transient increase in the cardiac biomarkers Troponin T (TnT) and NT-proBNP are observed during strenuous exercise, even in healthy athletes. Gut leakage, the translocation of bacterial lipopolysaccharide (LPS) into the circulation, is associated with atherosclerosis and cardiovascular disease, but has also been reported after prolonged endurance exercise. We aimed to explore the link between exercise-induced gut leakage and cardiac biomarker release. Methods: Participants in Norseman Xtreme Triathlon (Norseman) were included (n=42, age 43±9 years, 9 (21%) women). Blood samples were taken before, immediately after, and the day after the race for determination of gut leakage markers LPS, LPS-binding protein (LBP) and soluble cluster of differentiation 14 (sCD14), intestinal injury marker intestinal fatty-acid binding protein (I-FABP), TnT and NT-proBNP. Friedman tests, following Wilcoxon tests were applied for different time point comparisons, and Spearmans rho for correlation analyses. Results: Median finish time was 14h 33min (13h 42min, 15h 29min). TnT and NT-proBNP increased significantly to 38 ng/L (27, 56) and 495 ng/L (310, 828) after the race (p<0.001, both). LBP and sCD14 also increased significantly (p<0.001, both), as did I-FABP (p<0.01). LPS remained unchanged (p=0.13). No significant correlations between changes in gut leakage markers and changes in cardiac markers were observed after adjusting for multiple testing (p>0.05, all). Conclusions: In this cohort of Norseman Xtreme Triathlon participants, both cardiac and gut leakage markers increased after strenuous exercise, but were not intercorrelated. Thus, in healthy athletes, the exercise-induced increase in cardiac biomarkers and gut leakage seem to occur independently.